The basic discipline of psychiatry as metatext - Lolas Stepke, Fernando (Acta Bioethica, 2015)
Several disciplines converge on current psychiatric practice and research. Each one is a discourse with its defining objects, its audience and its socialization as specialized text. The psychophysiological triad includes studies of mentation (language), behavior and physiology. Each text is a context for the others. Thus, in and by itself, each one in isolation lacks explanatory power. The basic science of psychiatry is a metatext including those partial texts in a constructive fashion. Such an attempt is more a linguistic enterprise than an empirical one. It should supersede all reductionisms, including those presented in the form of juxtaposition of disciplines (bio-psycho-social, psycho-somatic, etc.).